Comparative Analysis of Performance of Cooperative Credit Method "PEARLS" - Susanto Wibowo; Rr. Dian Anggraeni; Etty Herijawati; Salikim Salikim (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
Credit unions are cooperatives that help their members to prosper, because it is built on the principle of mutual kegotong among members to help each other and help each other in relation to finance cooperative members. Purpose of this study will show the difference in the financial performance of “Asisi” credit cooperatives and credit unions “Puspita Kencana” using PEARLS. The method used there is a descriptive study using methods PEARLS and Statistical test with the sample collection technique using the "purposive sample" then test different descriptive statistics and Kruskal-Wallis test and test different significance with the Mann-Whitney U Sample data are secondary data from Kopdit financial statements mentioned above. The results showed the average value of the PEARLS method Kopdit “Puspita Kencana” results are better when compared to Koperasi Kredit “Asisi”. Then, with a significance difference test showed that the value Protect Liquid Effect and no significant difference of 0.008>0.05. While the value of Assets (0.310>0.05), Rates (0421>0.05) and Signs Growth (0222>0.05), there was no significant difference